EQ and SQ: how they relate to cognitive strategies to regulate emotion - Roslan, Samsilah; Mahyuddin, Rahil; Abu Bakar, Kamariah; Zakaria, Norhayati (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Self regulation of emotion refers to the skill and ability to handle different kinds emotions, especially those categorized as negative emotions. Inability to properly regulate emotions may lead to portrayal of unwanted or inappropriate behavior that can range from mild to extreme, including involvement in various kinds of behavioral problems. Therefore, regulation of emotion has been considered by experts as the key to understand and control behavior, especially among adolescents. Garnefski (2005) has identified 12 cognitive strategies that adolescents used to handle and overcome negative emotions. Based on Gross (2004) model of emotional regulation, it is stipulated that several internal and external factors may influence the usage of these cognitive strategies in regulating emotions. This study aims to look at how a person's level of emotional quotient and spiritual quotient were related to the usage of different cognitive strategies in regulating emotion. A total of 560 Form Four students from schools located in all the five zones in Malaysia (North, South, East Coast, Central and East Malaysia) were involved in the study. The findings showed that emotional quotient and spiritual quotient both have significant relationships with the usage of cognitive strategies in self regulation of emotion. The strength of relationship of EQ and SQ with self-regulation of emotion were stronger in the group of students with behavior problems with r= .47 and r= .42 respectively. Significant relationships were also found in students with good behaviour with r= .38 and r=.42 respectively. These findings have both theoretical and practical implications that are discussed in the paper.